Current Perspectives on Percutaneous Vertebroplasty: Current Evidence/Controversies, Patient Selection and Assessment, and Technique and Complications - Robert James Nairn; Shagran Binkhamis; Adnan Sheikh (Radiology Research and Practice)
Osteoporotic-associated vertebral compression fractures are a major public health concern, dwarfing even hip fractures in incidence in the United States. These fractures carry a significant morbidity and mortality burden and also represent a major growing source of consumption of scarce heath resources. Percutaneous vertebroplasty remains a commonly used and safe technique for the symptomatic treatment of vertebral compression fractures, both osteoporotic- and neoplastic-induced. By carefully selecting appropriate patients who are referred promptly, vertebroplasty can provide significant and durable pain relief over traditional conservative therapy. Recent controversies surrounding the evidence for vertebroplasty in osteoporotic-associated vertebral compression fractures are reviewed. A comprehensive step-by-step practical guide to performing vertebroplasty is then described. A brief description of patient selection, workup, as well as complications is also provided.